Effect of long term fertilization and manuring on soil quality and productivity under sorghum (Sorghum bicolor)-wheat (Triticum aestivum) sequence in Inceptisol - MALI, D V; KHARCHE, V K; JADHAO, S D; KATKAR, R N; KONDE, N M; JADHAO, S M; SONUNE, B A (The Indian Journal of Agricultural Sciences, 2015)
A permanent field experiment is continued since 1984-85 at Research Farm, AICRP on Cropping Systems Research Unit, Akola, Maharashtra with a view to find out effect of integrated nutrient management on soil quality and productivity of sorghum [Sorghum bicolor (L.) Moench] -wheat (Triticum aestivum L.) crop sequence. The long term impact of organic, inorganic and integrated nutrient management practices on soil quality and productivity were studied after 27th cycle (2010-11). The treatments comprised different levels of recommended dose of fertilizers (RDF), viz. 50, 75 and 100% and RDF in combination with farmyard manure, wheat straw, leucaena loppings and the farmer's practice. The results indicated that, application of 50% RDF + 50% N through FYM recorded highest sorghum (24.58 q/ha) and wheat (26.23 q/ha) grain yield as well as sorghum grain equivalent yield (61 q/ha). The uptake of N, P, K and S by sorghum (83.98, 23.14, 98.67 and 18.60 kg/ha) and wheat (96.17, 18.79, 74.69 and 13.53 kg/ha) was maximum with the integrated nutrient management. The improvement in soil fertility status was observed under the same treatment with concomitant increase in sustainability yield index (0.494) and soil quality index (2.33). The overall increase in the soil quality index (1.98-2.33) was recorded under INM, whereas only chemical fertilizers caused considerable decrease in the SQI (1.19-1.87). The hydraulic conductivity contributed substantially in governing sorghum yield (63.09%) and wheat yield (98.75%). The soil organic carbon contributed substantially in sorghum yield (29.01%). The parameters like hydraulic conductivity (94.7%), OC (5.14%) and DHA (0.07%) contributed in SQI.